1989
DOI: 10.1088/0953-4075/22/10/014
|View full text |Cite
|
Sign up to set email alerts
|

Interatomic potential for the B31 state of HgKr related to wing profiles of the Hg 253.7 nm line and to the vibronic spectrum of HgKr molecules

Abstract: The interatomic potential in the excited B31 state of HgKr is established and an estimation of the oscillator strength fXB is given by means of quantum calculations of suitable spectra of HgKr diatomics. Two kinds of experimentally examined spectra are taken into account: a thermally averaged 'hot' absorption spectrum occurring in the far wings of the Hg 253.7 nm line perturbed by Kr and a simple vibronic spectrum arising from B( nu '=0,. . .,14) from X( nu =0) transitions which was observed for supercooled mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…10a along with the results of Okunishi et al (13) and numerical values of Findeisen and Grycuk (8). The analysis carried out in Section 2A(a) indicated that the B state has a Morse-like character and only the long-range tail of its PE curve, very close to the dissociation limit, is dominated by a vdW component.…”
Section: C Long-range Correction To the B Morse-like Statementioning
confidence: 63%
See 4 more Smart Citations
“…10a along with the results of Okunishi et al (13) and numerical values of Findeisen and Grycuk (8). The analysis carried out in Section 2A(a) indicated that the B state has a Morse-like character and only the long-range tail of its PE curve, very close to the dissociation limit, is dominated by a vdW component.…”
Section: C Long-range Correction To the B Morse-like Statementioning
confidence: 63%
“…The long-range characteristic C 6 , obtained in this procedure, should be compared with those found in the literature: C 6 (6 3 P 1 ) = 1.350 (42) and 0.913 (43), and C 6 (B1) = 1.312 (7,8) and 1.527 (9), all in [cm −1Å 6 ] × 10 6 . Table 1 shows the results for the B1 state together with those determined in earlier investigations.…”
Section: A(a) the B1(6mentioning
confidence: 87%
See 3 more Smart Citations